The Legality Of Crypto Assets As A Means Of Debt Payment In Bankruptcy According To Civil Law And Bankruptcy Law - Sri Meliana Dewi, Alfat Hoki (International Significance of Notary, 2023)
Abstract :  Crypto assets have been regulated by the Commodity Futures Trading Supervisory Agency as tradable assets or commodities and not as a medium of exchange or payment. How is the legality of crypto assets and forms of legal protection for recipients of crypto assets as a means of debt payment in bankruptcy? The research method used in this study is normative legal research, which uses the statutory approach (statute approach) and conceptual approach (conceptual approach). The legal materials used are primary, secondary and tertiary legal materials and the legal material analysis techniques used in this study are qualitative descriptive analysis. The results of the study in saying that the legality of crypto assets as a means of debt payment in bankruptcy according to the Civil Code has binding force because it meets the legal requirements of the object of payment, so that crypto assets cannot be used as fulfillment of collection rights. The form of legal protection for recipients of crypto assets as a means of debt payment in bankruptcy is related to the payment process by the curator to creditors, the curator will settle the assets up to rupiah as stipulated in article 36 of Bappebti number 08 of 2021.Keywords: Legality, Crypto Asset, Debt Payment Instrument, Bankruptcy, Civil Law and Bankruptcy Law